Dynamic plasmonic beam shaping by vector beams with arbitrary locally linear polarization states - Man, Zhongsheng (2014)
Vector beams, which have space-variant state of polarization (SOP) comparing with scalar beams with spatially homogeneous SOP, are used to manipulate surface plasmon polarizations (SPPs). We find that the excitation, orientation, and distribution of the focused SPPs excited in a high numerical aperture microscopic configuration highly depend on the space-variant polarization of the incident vector beam. When it comes to vector beam with axial symmetry, multi-foci of SPPs with the same size and uniform intensity can be obtained, and the number of foci is depending on the polarization order n. Those properties can be of great value in biological sensor and plasmonic tweezers applications.